Global tectonics. - Kearey, P. (Wiley-Blackwell, 2009)
"The third edition of this widely acclaimed textbook provides a comprehensive introduction to all prospects of global tectonics. Revisions to this new edition reflect the most significant recent advances in the field, providing a thorough, accessible, and up-to-date text. Combining a historical approach with process science, Global Tectonics provides a careful balance between geological and geophysical material in both continental and oceanic regimes." "New and expanded chapters in this third edition include Precambrian tectonics and the supercontinent cycle; mantle processes, including mantle plumes; the implications of plate tectonics for environmental change; large igneous provinces; rifted continental margins; ocean ridges; continental transforms; subduction zones; and numerous orogenic examples. Written in an engaging style, this important text is an essential reference for undergraduates and graduate students who have a basic introduction in the geosciences."--BOOK JACKET.